Digital marketing and virtual try-on: A new ERA of online shopping - Le , Phuong Loan; Nguyen , Dang Phuong Anh; Le , Thi Ngan Hanh; Bui , Ngoc Tuan Anh (Journal of Finance - Marketing Research, 2025)
In the era of strong e-commerce development, attracting and retaining customers becomes extremely important. This topic focuses on two main factors, Virtual Try-on (VTO) and Digital Marketing (DM), to understand their impact on consumers' intention to purchase fashion products online. This is the first study with the aim of delving into the combined assessment of the impact of these two factors from a comparative perspective of perceived values in the field of online commerce. The study combines qualitative and quantitative research methods, in which the official survey was conducted within one month on the Google Form platform with 496 consumers in Ho Chi Minh City. Through data analysis using Smart-PLS 4.0, the results show that VTO positively affects the two intermediate values more than DM in this market. More notably, Perceived Hedonic Value has a superior impact than Perceived Utility Value when influencing purchase intention, indicating that both VTO and DM contribute greatly to increasing emotional factors in the shopping process. This study not only contributes to consolidating and expanding the theoretical basis of consumer behavior but also provides valuable information to help online fashion businesses improve their business efficiency by applying VTO popularly and optimizing DM, creating attractive shopping experiences, thus increasing sales and profits.